A contabilização dos ativos por impostos diferidos nos EUA e Europa e o efeito no investidor - Costa, P. (2015)
The accounting of the deferred tax assets is different whether it is used the International Accounting Standards Board (IASB) standards or it is used the Financial Accounting Standards Board (FASB) standards, in spite of all the convergence attempts. Therefore, we analyse which set of accounting standards, regarding the deferred tax assets, is more relevant for the investor, as well, which deferred tax assets are more value relevant, depending on their origin. Based on Ohlson (1995) model, we have concluded that the deferred tax assets are value relevant for the investor. We also have concluded that the accounting of the deferred tax assets using the FASB standards has greater value relevance than using the IASB standards. At least we have concluded that the deferred tax assets arising from deductible temporary differences are positively related with price, unlike the ones arising from losses and credit taxes that are negatively related with the price.